2020
DOI: 10.4236/as.2020.113017
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Potential of <i>Bacillus amyloliquefaciens</i> Bc2 and <i>Trichoderma harzianum</i> TR against Strawberry Anthracnose under Laboratory and Field Conditions

Abstract: The increasingly strict regulation of the use of phytosanitary products and the will of the populations to move towards sustainable development allow bio-sourced products and more particularly for biocontrol in the field of pesticides to progress. The study carried out here concerns the evaluation of the potency of Bacillus amyloliquefaciens Bc2 and Trichoderma harzianum to fight against strawberry cultures infected with anthracnose (Fragaria × ananassa Duch.). The studies were carried out in the laboratory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
0
5
0
2
Order By: Relevance
“…respectively (Table 2). The isolates were identified morphometrically, the Colletotrichum conidia were straight, cylindrical, with an obtuse apex and a truncated base; the average size was 13.2 x 4.2 μm, which correspond to the values indicated by Sutton 26 for Colletrotrichum gloesporioides. In the case of Lasiodiplodia conidia, the average size was 22.82 x 11.06 μm, located in the range indicated by Punithalingam 27 for Lasiodiplodia theobromae.…”
Section: Isolatesmentioning
confidence: 70%
“…respectively (Table 2). The isolates were identified morphometrically, the Colletotrichum conidia were straight, cylindrical, with an obtuse apex and a truncated base; the average size was 13.2 x 4.2 μm, which correspond to the values indicated by Sutton 26 for Colletrotrichum gloesporioides. In the case of Lasiodiplodia conidia, the average size was 22.82 x 11.06 μm, located in the range indicated by Punithalingam 27 for Lasiodiplodia theobromae.…”
Section: Isolatesmentioning
confidence: 70%
“…Previous research showed that T. harzianum and T. viride exhibited strong inhibitory activities against S. fuliginea , with 44.07% and 39.72% control efficiency, respectively ( 41 ). T. harzianum suppressed strawberry powdery mildew damping-off effectively ( 42 ). T. harzianum T39 spray reduced the severity of powdery mildew by 97%; however, as the epidemic progressed, its effectiveness dropped to 18 to 55% ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current context of global demands for the reduction of pesticides and agrochemicals (i.e. United States Environmental Protection Agency 2017), the identification of new biocontrol agents is essential for a sustainable agricultural practice (Berg 2009, Es-Soufi et al 2020. Native biodiversity can be a constant source of these new bioresources (i.e.…”
Section: Discussionmentioning
confidence: 99%